Reduced DNA methylation in Arabidopsis thaliana results in abnormal plant development - Finnegan, E.J. (Commonwealth Scientific and Industrial Research Organization, Canberra, ACT, Australia.); Peacock, W.J; Dennis, E.S (Proceedings of the National Academy of Sciences - PNAS, 1996)
Arabidopsis plants transformed with an antisense construct of an Arabidopsis methyltransferase cDNA (METI) have reduced cytosine methylation in CG dinucleotides. Methylation levels in progeny of five independent transformants ranged from 10% to 100% of the wild type. Removal of the antisense construct by segregation in sexual crosses did not fully restore methylation patterns in the progeny, indicating that methylation patterns are subject to meiotic inheritance in Arabidopsis. Plants with decreased methylation displayed a number of phenotypic and developmental abnormalities, including reduced apical dominance, smaller plant size, altered leaf size and shape, decreased fertility, and altered flowering time. Floral organs showed homeotic transformations that were associated with ectopic expression of the floral homeotic genes AGAMOUS and APETALA3 in leaf tissue. These observations suggest that DNA methylation plays an important role in regulating many developmental pathways in plants and that the developmental abnormalities seen in the methyltransferase antisense plants may be due to dysregulation of gene expression.